Potentials of intraesophageal рН-impedance measurement in GERD diagnostics - V. O. Kaybysheva; O. A. Storonova; A. S. Trukhmanov; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To demonstrate potentials and advantage of new method of gastroesophageal reflux disease (GERD) diagnostics – esophageal рН-impedance measurement.Key points. рН-impedance measurement of the esophagus allows to identify reflux episodes in the esophagus irrespective of refluxate рН. In contrast to traditional pH-metry the new method represents physical state of refluxate (gas, fluid, mixed contents), time of volume clearance to determine relation of observed symptoms to non-acidic refluxes. This promotes improvement of diagnostics and treatment of GERD.Conclusion. Application of esophageal рН-impedance measurement allows to consider this method as the most exact and modern in diagnostics of GERD.